2012
DOI: 10.2478/s11532-012-0063-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary calculi — atypical source of information on mercury in human biomonitoring

Abstract: Abstract:© Versita Sp. z o.o. Chemical analysis of various biological matrices is routinely used for assessment of human exposure to various toxic metals. In this work, 489 samples of urinary calculi originating from almost the whole of The Czech Republic, were collected and subjected to mineralogical and elemental analysis. This study was aimed at mercury, the content of which was determined using thermo-oxidation -cold vapor -atomic absorption spectrometry. The effects of mineralogical composition, sex, age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Significant differences (p \ 0.001) were found for all tested elements except for K (p = 0.267). Similar results were found in our previous work with exception for Cr and Se where no significant difference was detected (Kuta et al 2013(Kuta et al , 2012. This is in agreement with work of Bazin and Giannossi (Bazin et al 2007;Giannossi et al 2013) who reported higher contents of metal elements in calcium oxalates (whewellite and weddellite) compared to uric acid stones.…”
Section: Contents Of Elements In Whewellite and Uric Acid Stonessupporting
confidence: 94%
See 1 more Smart Citation
“…Significant differences (p \ 0.001) were found for all tested elements except for K (p = 0.267). Similar results were found in our previous work with exception for Cr and Se where no significant difference was detected (Kuta et al 2013(Kuta et al , 2012. This is in agreement with work of Bazin and Giannossi (Bazin et al 2007;Giannossi et al 2013) who reported higher contents of metal elements in calcium oxalates (whewellite and weddellite) compared to uric acid stones.…”
Section: Contents Of Elements In Whewellite and Uric Acid Stonessupporting
confidence: 94%
“…Another important fact is that urinary stones can be considered as ''waste'' material in hospitals and therefore can be potentially available for analysis. As far as authors know, only a few studies were published regarding differences in contents of trace element in urinary stones related to geographical conditions (Kuta et al 2012;Pineda-Vargas et al 2009, smoking (Slojewski et al 2009) or to the effect of sex and age (Kuta et al 2012). However, use of urinary stones for biomonitoring can be limited by known mutual association of trace and minor elements with mineral constituents (Giannossi et al 2013;Abboud 2008a;Bazin et al 2007;Kuta et al 2013;Slojewski et al 2010;Wandt and Underhill 1988).…”
Section: Introductionmentioning
confidence: 95%
“…An interesting use of CV-AAS was reported by Kuta et al 76 for the determination of Hg in human urinary calculi from 489 samples taken from across the Czech Republic. Direct solid sampling was employed through the use of thermo-oxidation which enabled an LOD of 0.0001 mg kg À1 .…”
Section: Atomic Uorescence Spectrometry and Vapour Generation Procedmentioning
confidence: 99%
“…Both analytical procedures have already been reported elsewhere. 51,53 The results of solution ICP-MS analysis slightly differ in some cases from those of IR screening, which probably results from the fact that each of the halves of a particular kidney stone was crushed and homogenized separately with the assumption that a kidney stone is approximately radially symmetric.…”
Section: Elemental Composition Of Urolithsmentioning
confidence: 99%